Patients With Heart Failure in the Intermediate Range of Peak Oxygen Uptake - Ritt, Luiz Eduardo Fontele [UNIFESP] (2012)
PURPOSE: While patients with heart failure who achieve a peak oxygen uptake (peak (V) over dotO(2)) of 10 mL.kg(-1).min(-1) or less are often considered for intensive surveillance or intervention, those achieving 14 mL.kg(-1).min(-1) or more are generally considered to be at lower risk. Among patients in the intermediate range of 10.1 to 13.9 mL.kg(-1).min(-1), optimally stratifying risk remains a challenge.METHODS: Patients with heart failure (N = 1167) referred for cardiopulmonary exercise testing were observed for 21 +/- 13 months. Patients were classified into 3 groups of peak (V) over dotO(2) (<= 10, 10.1-13.9, and >= 14 mL.kg(-1).min(-1)). the ability of heart rate recovery at 1 minute (HRR1) and the minute ventilation/carbon dioxide output ((V) over dotE/(V) over dotCO(2)) slope to complement peak (V) over dotO(2) in predicting cardiovascular mortality were determined.RESULTS: Peak (V) over dotO(2), HRR1 (<16 beats per minute), and the (V) over dotE/(V) over dotCO(2) slope (> 34) were independent predictors of mortality (hazard ratio 1.6, 95% CI: 1.2-2.29, P = .006; hazard ratio 1.7, 95% CI: 1.1-2.5, P = .008; and hazard ratio 2.4, 95% CI: 1.6-3.4, P < .001, respectively). Compared with those achieving a peak (V) over dotO(2) >= 14 mL.kg(-1).min(-1), patients within the intermediate range with either an abnormal (V) over dotE/(V) over dotCO(2) slope or HRR1 had a nearly 2-fold higher risk of cardiac mortality. Those with both an abnormal HRR1 and (V) over dotE/(V) over dotCO(2) slope had a higher mortality risk than those with a peak (V) over dotO(2) <= 10 mL.kg(-1).min(-1). Survival was not different between those with a peak (V) over dotO(2) <= 10 mL.kg(-1).min(-1) and those in the intermediate range with either an abnormal HRR1 or (V) over dotE/(V) over dotCO(2) slope.CONCLUSIONS: HRR1 and the (V) over dotE/(V) over dotO(2) slope effectively stratify patients with peak (V) over dotO(2) within the intermediate range into distinct groups at high and low risk.